Experimental Validation of N2 Emission Ratios in Altitude Profiles of Observed Sprites - Kuo, Cheng-Ling; Williams, Earle; Adachi, Toru; Ihaddadene, Kevin; Celestin, Sebastien; Takahashi, Yukihiro; Hsu, Rue-Ron; Frey, Harald U.; Mende, Stephen B.; Lee, Lou-Chuang (Frontiers in Earth Science, 2021)
Recent efforts to compare the sprite ratios with theoretical results have not been successfully resolved due to a lack of theoretical results for sprite streamers in varying altitudes. Advances in the predicted emission ratios of sprite streamers with a simple analytic equation have opened up the possibility for direct comparisons of theoretical results with sprite observations. The study analyzed the blue-to-red ratios measured by the ISUAL array photometer (AP) with the analytical expression for the sprite emission ratio derived from the modeling of downward sprite streamers. Our statistical studies compared sprite halos and carrot sprites where the sprite halos showed fair agreement with the predicted ratios from the sprite streamer simulation. But carrot sprites had lower emission ratios. Their estimated electric field has a lower bound of greater than 0.4 times the conventional breakdown electric field (Ek). It was consistent with the results of remote electromagnetic field measurements for short delayed or big/bright sprites. An unexpectedly lower ratio in carrot sprites occurred since sprite beads or glow in carrot sprites may exist and contribute additional red emission.